Legaran Demokrasi: Kolaborasi Nyanyian Mentawai dan Legaran Randai Minangkabau dalam Perspektif Seni Pertunjukan - M. Arif Anas; Martis Martis (LPPM Institut Seni Indonesia Padangpanjang, 2025)
The composition â€œLegaran Demokrasiâ€ is an artistic representation of the cultural dynamics of Minangkabau and Mentawai within the framework of interpreting the contemporary democratic system. Through a collaborative approach, this work explores the fusion of traditional Mentawai songs and the legaran randai of Minangkabau, arranged in a multi-part dramatic structure and accompanied by the use of non-conventional instruments such as sewing machines, vacuum cleaners, and sarongs. This work not only emphasizes innovation in the musical aspect but also affirms that art forms can serve as reflective media for social issues such as the marginalization of local cultures, the transformation of collective values, and the shifting of identities in the current of globalization. The creative process was carried out through stages of exploration, improvisation, and formation, culminating in a theatrical presentation with an interactive format and collective narrative. The symbolism of movement, sound, and bodily formations is interpreted as a visualization of the spirit of musyawarah (deliberation) and mufakat (consensus) that underlies democracy in the Minangkabau context. The results demonstrate that cross-cultural and cross-media approaches can open new spaces in the creation of contemporary performing arts while remaining rooted in tradition. This finding reinforces the idea that cultural preservation does not necessarily require the perpetuation of old forms but can be achieved through innovations that are sensitive to local values and open to the interpretations of the times.